2009
DOI: 10.1017/s1479262109990098
|View full text |Cite
|
Sign up to set email alerts
|

Genetic reticulation and interrelationships amongcitrullusspecies as revealed by joint analysis of shared AFLPs and species-specific SSR alleles

Abstract: Thirty-one accessions of Citrullus spp. belonging to Citrullus lanatus var. lanatus, C. lanatus var. citroides and Citrullus colocynthis were subjected to phylogenetic analysis using combined datasets of amplified fragment length polymorphisms (AFLPs) and simple sequence repeats (SSRs). Tree topologies inferred by neighbour-joining analysis have resolved the phylogenic relationships among the species with special reference to established taxonomic classification. In this study, we have clearly resolved species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…egusi (Fursa, 1972;Jeffrey, 2001) and have sometimes been misclassified as C. colocynthis (Gusmini et al, 2004;Jarret et al, 1997;Robinson and Decker-Walters, 1997;Wehner, 2008). However, chloroplast (Dane and Lang, 2004;Dane and Liu, 2007) and nuclear (Che et al, 2003;Jarret et al, 1997;Nimmakayala et al, 2010) genetic studies do not support the subspecies classification and groups egusi types with cultivated watermelon (Citrullus lanatus var. lanatus).…”
mentioning
confidence: 94%
“…egusi (Fursa, 1972;Jeffrey, 2001) and have sometimes been misclassified as C. colocynthis (Gusmini et al, 2004;Jarret et al, 1997;Robinson and Decker-Walters, 1997;Wehner, 2008). However, chloroplast (Dane and Lang, 2004;Dane and Liu, 2007) and nuclear (Che et al, 2003;Jarret et al, 1997;Nimmakayala et al, 2010) genetic studies do not support the subspecies classification and groups egusi types with cultivated watermelon (Citrullus lanatus var. lanatus).…”
mentioning
confidence: 94%
“…However, this was lower than 133, 101 and 795 alleles detected by Zhang et al (2016), Wang et al (2015) and Reddy et al (2015) among watermelon accessions, respectively. Nimmakayala et al (2009) reported a total of 169 alleles amplified in watermelon accessions. In the current study the number of alleles per locus ranged from 2 to 19, with a mean of 9.4.…”
Section: Discussionmentioning
confidence: 99%
“…Guerra-Sanz (2002) reported 1-8 alleles in C. lanatus genotypes and varieties, 0-2 alleles in C. colocynthis genotypes, and 0-4 alleles in hybrids by using 18 SSR markers. In another study, Nimmakayala et al (2010) estimated the phylogenetic relations of 31 accessions of C. lanatus var. lanatus, C. lanatus var.…”
Section: Discussionmentioning
confidence: 99%